The impact of human resources management automation on increasing employee productivity at the Tabuk Region Municipality: A field study (The International Journal for Scientific Research, 2026)
This research aims to investigate the impact of human resource management automation on enhancing employee productivity at the Tabuk Region Municipality, employing a descriptive quantitative approach. The research population comprised human resource management staff and relevant experienced personnel, with a random sample of 193 employees selected. Data were collected via a specially designed questionnaire and statistically analyzed using SPSS and AMOS software packages.The results revealed a statistically significant positive impact of automation on productivity levels. Analysis models showed that automation explained approximately 87.3% of the variance in productivity levels, with a standard regression coefficient of 0.934. The study also highlighted the pivotal role of automation in enabling efficient remote work during the COVID-19 pandemic, contributing to the continuity of administrative processes and mitigating the risk of pandemic spread. This effectiveness was widely supported by the sample. The analysis revealed strong positive correlations between automation and improved human resources management functions (r = 0.958), and between automation and the actual degree of automation implementation in the municipality's departments (r = 0.928). Furthermore, automation was positively correlated with the effectiveness of remote work during the pandemic (r = 0.602).Based on these findings, the study recommends the institutional expansion of technological solutions and process automation within the human resources department of the Tabuk Municipality. This is due to its direct contribution to increasing operational efficiency, expediting recruitment and training procedures, and improving the quality of services provided to employees, thereby enhancing organizational effectiveness and supporting the achievement of strategic objectives. It is expected that implementing these recommendations will contribute to improving the performance of relevant departments and enhancing the outputs of services provided to both employees and the community.
Keywords: Human Resources Management Automation; Employee Productivity; Remote Work; COVID-19 Pandemic; Tabuk Municipality